KEMAMPUAN PEMECAHAN MASALAH MAHASISWA DALAM MENYELESAIKA SOAL KALKULUS DIFERENSIAL PADA MASA PEMBELAJARAN ONLINE - Eka Nurmala Sari Agustina; Siti Nuriyatin (JEDMA Jurnal Edukasi Matematika, 2023)
The research conducted at the end of this semester aims to describe the condition of students' problem-solving abilities in differential calculus courses during online lectures during a pandemic. The research involved 10 second-semester students who were given 3 test questions related to derivative rules, implicit functions, and practical problems. The results of student answers are given a score of 0 – 4 to determine the level of problem-solving ability. Then 3-5 students were selected for each question according to the level of problem-solving ability to describe their problem-solving abilities. It was found that students do not always have high problem-solving abilities on a problem, they also have high problem-solving abilities on other problems. Students tend to make problem-solving mistakes on implicit function questions and practical problems. Errors are caused by students not understanding the variables that are implicit functions and tend to make these variables into coefficients. Students also have difficulty forming appropriate mathematical models from questions in the form of contextual problems.